Socioeconomic Status and Its Impact on Language Development in Preschool Children in South Sudan - Akol, Ayen (International Journal of Linguistics, 2024)
Purpose: The aim of the study was to analyze the socioeconomic status and its impact on language development in preschool children. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Socioeconomic status significantly influences language development in preschool children, with higher SES linked to better language skills. Disadvantaged backgrounds often correlate with delayed language acquisition and poorer linguistic abilities. Factors like access to resources and parental education impact language outcomes. Unique Contribution to Theory, Practice and Policy: Social interactionist theory, the theory of cultural capital & the ecological systems theory may be used to anchor future studies on socioeconomic status and its impact on language development in preschool children. Provide professional development opportunities for educators and caregivers to enhance their understanding of the impact of socioeconomic factors on language development and equip them with effective strategies for addressing language disparities in diverse preschool settings. Advocate for policies that prioritize equitable access to high-quality early childhood education and childcare services, including targeted funding initiatives aimed at improving resources and staffing ratios in preschools serving low-income communities.